Distinct vertical behavior of key Arctic copepods following the midnight sun period in the East Siberian continental margin region, Arctic Ocean - Son, Wuju; Kim, Jee-Hoon; Yang, Eun Jin; La, Hyoung Sul (Frontiers in Marine Science, 2023)
Diel vertical migration (DVM) of zooplankton plays a vital role in biological carbon pump and food web interactions. However, there is considerable debate about the DVM of zooplankton in response to environmental changes in the Arctic Ocean. We investigated DVM behavior in the key Arctic copepods Calanus glacialis, Calanus hyperboreus, and Metridia longa following the midnight sun period in the East Siberian continental margin region. The two Calanus species showed non-DVM behaviors, whereas M. longa showed a typical DVM pattern consistent with the solar radiation cycle. Additionally, these species showed different vertical distributions. Calanus glacialis was distributed at depths above 20 m in the warm fresh water, where the highest density gradient was observed. Calanus hyperboreus was distributed at depths between 30 and 55 m in the cold salty water, where a high contribution of micro phytoplankton and the subsurface chlorophyll maximum (SCM) layer were observed. M. longa was found across a broader range of temperature and salinity than both Calanus species, and it was distributed in the upper water column, where the SCM layer was observed at night and at depths between 100 and 135 m in the daytime. These results imply that M. longa can be well adapted to the changing Arctic Ocean environment, where sea ice loss and ocean warming are ongoing, whereas C. hyperboreus can be the most vulnerable to these changes. These findings provide important information for understanding variations in the vertical distributions of key copepod species in the rapidly changing Arctic marine environment.